On a family of surfaces with common asymptotic curve in the Galilean space G3 - Yuzbasi, Zuhal Kucukarslan (Int Scientific Research Publications, 2016)
In this paper, we obtain the parametric representation for a family of surfaces through a given asymptotic curve by using the Frenet frame in the Galilean space G(3). Necessary and sufficient conditions are given for that curve to be an isoasymptotic curve on the parametric surfaces. We also provide an example in support of our results. (C) 2016 All rights reserved.
Keywords: Asymptotic curve; parametric surface; Galilean space